ESTIMATIONS OF LOCAL MAGNETIC FIELDS IN SOLAR FLARES: BASIC METHODS AND SOME RESULTS - Lozitsky, V. G.; Baranovsky, E. A.; Lozitska, N. I.; Tarashchuk, V. P. (Одеські астрономічні публікації, 2017)
We consider three methods for estimations of local magnetic fields in solar flares: (1) analysis of bisectors of I ± V profiles (Lozitsky, 2015); (2) search for Zeeman-like effects in cores of spectral lines with very low Lande factors, geff ≈ 0.01 (Lozitsky, 1993, 1998); (3) semi-empirical modeling using many spectral lines and two-component models (see, e.g., Lozitsky et al., 2000). We illustrate the application of named methods to different observational data and to different spectral lines. Our main conclusions are following: (a) upper limit of local magnetic fields in solar flares is, at least, 104 G, (b) such extremely strong fields can occur in very small, spatially unresolved scales, (c) lifetime of such fields is, at least, a few minutes.